Efficiency of Various Tubular Occlusion Agents in Human Dentin after In-Office Tooth Bleaching - Natalia Papazisi; Dimitrios Dionysopoulos; Olga Naka; Dimitris Strakas; Sotiria Davidopoulou; Kosmas Tolidis (Journal of Functional Biomaterials, 2023)
The aim of this laboratory study was to investigate and compare the impact of five desensitizing techniques as a treatment fortooth sensitivity on the exposed dentin after an in-office tooth bleaching procedure. Thirty intact human molars were collected for this investigation. The specimens were obtained by transversely cutting 2.5 mm of the crowns, leading to exposure of the dentin. The specimens were cleaned in an ultrasonic bath and treated initially with EDTA gel 15% for 4 min and then with Opalescence Boost bleaching gel (40% H2O2) for two sets of 20 min. Then, the samples were randomly divided into six groups (n = 5) and received one of the following treatments: Group 1 (no treatment—control group), Group 2 (Emofluor gel—0.4% SnF2), Group 3 (MI Paste—CPP-ACPF), Group 4 (BioMinF paste—calcium phospho-fluoro-silicate), Group 5 (air-abrasion with ProSylc—Bioglass 45S5), and Group 6 (Er,Cr:YSGG laser). Subsequently, each sample was observed utilizing scanning electron microscopy (SEM) in order to detect the rate of occlusion of dentin tubules. SEM-EDS analysis revealed no occlusion of the dentin tubules in the control group, while Groups 2, 4, and 5 presented high effectiveness (>95% percentage of occluded tubules), and Groups 3 and 6 presented lower values (21.6 and 26.8%, respectively). It was concluded that althoughall the tested groups presented higher percentages of occlusion of the dentinal tubules compared to the control group, there were differences in effectiveness among them. The most effective treatments were the daily use of BioMinF paste and SnF2-containing gel, as well as air-abrasion with ProSylc powder.